Gambaran Kejadian IMLTD pada Pendonor Darah di UPT Transfusi Darah Dinas Kesehatan Provinsi Sulawesi Selatan Tahun 2024 - Hardiyanti Julia Rahmat; Dahniar Dahniar; A. Arviani Desianti Nur (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
A donor is someone who gives blood or blood components so that they can be used by others. Blood transfusion is a blood or blood components distribution activity from donors to patients with special considerations. Blood transfusion carry the risk of transmitting infection that can endanger the recipient patients. Transfusion-transmitted infections are pathogens that can weakenbthe immune system. These infections can include HIV, HBsAg, HCV, and Syphilis. Pre-transfusion screening is necessary to minimize the risk of infection spread. Pre-transfusion screening tests that can be performed include chemiluminescent immunoassay (CHLIA) and nucleic acid testing (NAT). These tests can detect the presence and quantify the titer of antigens in the serum and blood of potential donors. Screening for transfusion-transmitted infections is a blood safety measure aimed at minimizing the risk of infection transmission to blood recipients, healthcare workers, and the environment, conducted prior to the blood transfusion process. The high incidence of Transfusion-Transmitted Infections in donor blood units underscores the importance of accurate and precise screening. Testing must have high sensitivity and specificity to prevent false-negative results due to low analyte levels.